(untitled) - Bentley, Jerry H. (Boston, 2006)
Traditions & Encounters: A Brief Global History, the highly-anticipated concise version of Bentley and Ziegler's best-selling survey text, provides a streamlined account of the cultures and interactions that have shaped world history. With an engaging narrative, strong thematic approach, visual appeal, and solid pedagogy, it offers enhanced flexibility and affordability without sacrificing the features that have made the complete text a favorite among instructors and students alike
Keywords: Intercultural communication,Lịch sử thế giới,World history; History,Giáo trình